Determinants of hypertension among urban adult population in Kancheepuram district of Tamil Nadu - S., Gopalakrishnan; R., Rama; A. K., Savitha (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension affects approximately 1 billion people worldwide and around 7.1 million deaths per year (13% of the total) may be attributable to it. In India, the overall prevalence of raised blood pressure among adults aged 18 years and above was estimated to be 25.9% among males and 24.8% among females. Keeping in mind the growing burden of NCDs like hypertension, this study was conducted with the objective to estimate the prevalence of hypertension and its associated determinants so as to understand the gravity of the problem and to plan possible corrective measures. Methods: This community based cross sectional study was done among adult population in an urban area in Kancheepuram district using a sample size of 1634 calculated based on the prevalence of a previous study. Probability Proportion to Size and simple random sampling method was used. A structured questionnaire was used to collect data and data analysis was carried out using SPSS version 15 by calculating appropriate percentages and strength of association of variables. Results: This study results shows that the prevalence of pre – hypertension was 51.3% (males 54.2% and females 48.5%). Overall prevalence of stage I hypertension was 17.2% (males 20.2% and females 14.4%), stage II hypertension was 5.2% (males 6.3% and females 4.2%). A statistical significant association was found between hypertension and its associated determinants such as increasing age, gender (male predominance), history of diabetes mellitus and overweight/obesity (P value <0.05). Conclusions: This study outcome shows that the prevalence of pre-hypertension and hypertension is high among the adult population. For non-communicable diseases like hypertension every level of preventive care plays a major role to bring about a healthy behaviour and lifestyle change among the population which in turn will help in reducing the morbidity and mortality due to cardiovascular diseases.